D/L arabinitol Ratio as an Indicator of a Healthy Lifestyle. A preliminary Study (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
D-arabinitol, as opposed to the L-arabinitol, is produced by fungi of the genus Candida. The increasedD/L-arabinitol ratio in body fluids is a recognized biomarker of systemic fungal infection . The factors which increase the risk of candidiasis include: sugar and confectionery, sweetened sodas, alcohol, beer, coffee, black tea, red meat, refined flour products, tobacco and salt. Often, vitamin deficiencies are caused by candidiasis of the colon. The D/L ratios in urine were determined by gas chromatography with electron capture detection (GC-ECD). For 21 examined students a questionnaire survey related to their healthy lifestyle was conducted. The lower D/L ratio in the urine of students declaring regular intake of vitamin supplements and daily consumption of fruits and/or vegetables to improve their immunity against diseases was observed. The D/ L ratio may be considered a potential indicator of a healthy lifestyle, especially in the case of young people.